Toxicity Test of Sentul Fruit (Sandoricum koetjape) Peel Extract on Mice - I Nyoman Wirata; Anak Agung Gede Agung; Ni Wayan Arini; I Gusti Ayu Raiyanti; I Gusti Agung Ayu Novya Dewi (Indonesian Journal of Medicine, 2023)
Background: Sentul fruit peel extract has an antibacterial activity since it contains saponin, flavonoid, phenol, and tannin. Hence, it can be utilized in oral infection treatment. The safety level of herbal medicines needs to be studied by using a toxicity test. The study aims to discover the toxicity of Sentul fruit peel extract.Subjects and Method: The study was conducted in the laboratory of the Faculty of Food Technology of Warmadewa University and the laboratory of the Faculty of Medicine and Health Sciences of Warmadewa University. The independent variables of the study were the various doses of Sentul peel extract administered orally. The dependent variable was an acute toxicity test. The toxicity test in mice used an experimental study design in the laboratory that was observed qualitatively and quantitatively. The animals used were 25 male white mice (Mus musculus) and were divided into 5 groups. Data were collected based on the results of examinations from the laboratory and subsequently analyzed qualitatively and descriptively.Results: Based on the results of the LD50 Toxicity Test on Mice, Sentul peel extract samples did not cause toxic symptoms in the form of decreased heart activity, convulsions, decreased movement activity, and slow breathing. The administration of Sentul peel extract was categorized as non-toxic because mice do not experience abnormal symptoms and there was no death after the administration of the extract using the oral gavage method at all doses for 14 days, thus Sentul peel extract was safe to use as a medicinal ingredient.Conclusion: Sentul peel extract is categorized as non-toxic because mice do not experience abnormal symptoms and no death occurs.Keywords: Sentul peel, extraction, oral infection, mice, toxicityCorrespondence: I Nyoman Wirata, Health Polytechnic of the Ministry of Health Denpasar. Jl. Sanitasi No.1, Sidakarya, South Denpasar, Denpasar City, Bali 80224. Email: wiratainyoman@gmail.com. Mobile: 08123649998.Indonesian Journal of Medicine (2023), 08(01): 114-120https://doi.org/10.26911/theijmed.2023.08.01.11